Internal root resorption and periapical pathoses as dental complication of herpes zoster infection: Report of rare case with review of literature - Praveena Geetha; Rathy Raveendran; Thekkekara Pushkaran Padmakumar (Wolters Kluwer Medknow Publications, 2014)
Herpes zoster (HZ) is an uncommon acute viral infection caused by reactivation of varicella zoster virus. The maxillofacial surgeon should be aware of the less recognized maxillofacial complications, which include facial scarring, irregular short roots, osteonecrosis, exfoliation of teeth, periodontitis, calcified and devitalized pulps, internal root resorption, periapical pathoses. Here, we report a case of 47-year-old man presented with multiple internal root resorption and periapical pathoses in upper left quadrant 20 years after the attack of HZ of the maxillary division of the trigeminal nerve of the same side. The literature is reviewed with emphasis on etiology and diagnosis.